Decision Rules and Transactions, Organizations and Markets - Baligh, Helmy H. (Management Science, 1986)
Organizations and markets are defined as sets of people who are connected together by the logical orders of decision rule and transaction respectively. Super organizations are defined as sets of organizations connected by decision rules. The logical order is the basis of an arrangement of people or organizations. These concepts are developed in an unambiguous manner, and used to produce analytically useful definitions of pure and hybrid classes. The concepts are shown to be of value in the analysis of organizations and markets. The concept of the decision rule is used to define static organization structures, and to define dynamic task processes in them. Generalizations about organizations and markets are developed and put together to get new ones. Two classification schemes in the literature are simplified by a redefinition of their classes in terms of decision rules only. This not only integrates two seemingly different schemes, but it illustrates how useful the concept of the decision rule could be in analyzing and generalizing about organizations, other arrangements of persons, and arrangements of arrangements of persons.